Rubber-Derived Sulfur Composite Cathode Material for Li-S/Li-ion Battery - Akihiro YAMANO; Tatsuya KUBO; Fumiya CHUJO; Naoto YAMASHITA; Takashi MUKAI; Masanori MORISHITA; Toshikatsu KOJIMA; Masahiro YANAGIDA; Kazuo HOCHI; Satoshi FURUSAWA; Naohiko KIKUCHI; Tetsuo SAKAI (Electrochemistry, 2022)
A rubber-derived sulfur composite cathode material for the Li-S battery/Li-ion battery was synthesized by the vulcanization process of butadiene rubber as a polymer source and a large amount of sulfur. In this study, the higher vulcanization temperature of 450 °C and a larger amount of sulfur (rubber : sulfur = 1 : 10, mass/mass) than the mass production process of the rubber were applied. The rubber-derived sulfur composite has a large amount of sulfur, ca. 58 wt% and a stable cycling ability with a capacity of 400 mAh g−1 at 30 °C. The cells consisting of the rubber-derived sulfur composite as the cathode and SiO as the anode displayed a great potential as for the next-generation LIBs because of its both electrodes containing no transition metals, outstanding electrochemical properties and safety performance. The cell showed a superior high and low temperature performance from −20–80 °C for over 100 cycles and a good rate performance in which the capacity of ca. 600 mAh g−1 was obtained at the 5 C-rate at 60 °C. In addition, there were no thermal runaway and no evolution of hydrogen sulfide in the nail penetration test.